Nursing students' perceptions regarding well-being and healthy use of digital technology: A qualitative thematic analysis - Maya Sahu; Sailaxmi Gandhi; Manoj Kumar Sharma; Seema Mehrotra (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The health and well-being of nursing students are of the utmost importance. Well-being is affected by many factors, ranging from day-to-day hassles to severe stressors in students' college lives. In addition to many other challenges, one new component is added with the advancement of technology, that is, the use of digital technology. The objectives of the study were to explore the perceptions of nursing students regarding well-being, its associated factors, digital technology usage and association between well-being and digital technology use. MATERIALS AND METHODS: A qualitative descriptive design using focus group discussion (FGD) was adopted in this study. A purposive sampling technique was followed for selecting the participants. Five nursing colleges in the city of Bengaluru from Karnataka state (Central Government-1, State Government-2, and Private-2) were selected based on their willingness to allow their students to be a part of the study. Around 12-15 students from each college who might provide potentially rich data were invited to participate in the study. Six FGDs were conducted during June-August 2018 with a total of 80 participants. All the participants were informed about the study. Written informed consent was obtained. All FGDs were audio recorded, and audiotapes were transcribed. Thematic analysis was done using Atlas.ti software. RESULTS: The emerging themes were clustered under the following broad categories: understanding the concept of well-being and associated factors; understanding digital technology; ways to healthy use of digital technology; strategies to maintain well-being; and a felt need for professional help. CONCLUSION: This study provides an insight into the experiences of well-being, stress, and use of digital technology among undergraduate nursing students. The findings have led to elicit the components required to develop an intervention program that may help the undergraduate nursing students to enhance well-being as well as promote healthy use of digital technology.